2016
DOI: 10.12669/pjms.326.10905
|View full text |Cite
|
Sign up to set email alerts
|

Serum C-reactive protein level in COPD patients stratified according to GOLD 2011 grading classification

Abstract: Background and Objective:The Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2011 grading classification has been used to evaluate the severity of patients with chronic obstructive pulmonary disease (COPD). However, little is known about the relationship between the systemic inflammation and this classification. We aimed to study the relationship between serum CRP and the components of the GOLD 2011 grading classification.Methods:C-reactive protein (CRP) levels were measured in 391 clinically sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…It was further established that patients presenting with acute exacerbation had higher levels of acute phase proteins like CRP than stable patients [20] . In our study, CRP is inversely correlated with FEV1(r= -0.284, p=0.004) that was statistically significant which is in accordance with study conducted by SJ Wu,PChen et al [21] , Andrea Corsonello et al [22] and Yihua Lin [23] who also found negative correlation of CRP with FEV1. Study by Rakesh Kumar and P Nigam [24] concluded that correlation of CRP with FEV1 was negative in cases presenting as acute exacerbation.…”
Section: Discussionsupporting
confidence: 91%
“…It was further established that patients presenting with acute exacerbation had higher levels of acute phase proteins like CRP than stable patients [20] . In our study, CRP is inversely correlated with FEV1(r= -0.284, p=0.004) that was statistically significant which is in accordance with study conducted by SJ Wu,PChen et al [21] , Andrea Corsonello et al [22] and Yihua Lin [23] who also found negative correlation of CRP with FEV1. Study by Rakesh Kumar and P Nigam [24] concluded that correlation of CRP with FEV1 was negative in cases presenting as acute exacerbation.…”
Section: Discussionsupporting
confidence: 91%
“…The overall prevalence of spirometry-defined COPD was 8.6%, accounting for 99.9 million people with COPD in China [2]. More and more studies have shown that COPD is not only a respiratory inflammatory condition, but also one disease characterized by low-grade and chronic systemic inflammation with many extrapulmonary manifestations [3,4]. The systemic inflammation is associated with lung function, exercise capacity, degree of dyspnea, arterial oxygen tension, clinical outcome, risk of exacerbation, and all-cause and COPD-related mortalities [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical symptoms and a high risk of exacerbations were observed in COPD patients of group D[ 15 ], whose CRP values were significantly higher than those in the other three groups[ 16 ]. Thus, a clinical trial was conducted to investigate the effects of tiotropium (Tio) and/or budesonide/formoterol (Bud/Form) on systemic inflammation biomarkers in stable COPD patients of group D and improvements of symptoms and pulmonary function.…”
Section: Introductionmentioning
confidence: 99%